Perlindungan Hukum Terhadap Anak Akibat Dari Perkawinan WNI Dengan WNA Di Kecamatan Cisarua Kabupaten Bogor - Agung Wiraguna; Kholil Nawawi (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Country marriages are not new to Indonesia's multicultural society. Such marriages take place in the midst of society (in various social dimensions) and have been going on for a long time. However, that does not mean that the issue of Country marriage is not a problem, in fact it tends to always generate controversy in the community. There is an assumption that the cause is the existence of Law no. 1 of 1974 which does not accommodate the problem of Country marriage, because the mixed marriage referred to in Article 57 of the UUP is a marriage between two people who are subject to different laws, due to differences in nationality, not due to differences in religion.The purpose of writing this thesis is to be able to know, understand and analyze thoroughly or in depth about Country marriage according to Islamic Law, Civil Law and laws and regulations in Indonesia, and also want to know the factors of Country marriage and the problems or problems that arise due to Country marriage. The method used in this research is qualitative. This data collection technique is carried out using literature review, namely by collecting data and looking for ideas, theories, opinions, or findings that are closely related to the subject matter. The results showed that based on the Al-Quran letter Al-Baqoroh: 221, Law No. 1 of 1974 Article 2 paragraph (1), KHI, Articles 4, 40 and 44 all prohibit Country marriages. Because it is not in accordance with the purpose of marriage, namely to achieve a happy and eternal family based on the almighty God, Meanwhile, Marriage in the Civil Code / Burgerlijk Wetboek Article 26 is stated in article 26 BW "The law views the matter of marriage only in civil relations" However, with the existence of Marriage Law Article 166, the provisions stipulated in the Civil Code are declared invalid. The problems caused by Country marriage are divided into two, namely the psychological aspect and the juridical aspect. Psychologically, Country marriage can have an impact on the harmony of the household that will be lived. Then when viewed using juridical glasses, it is closely related to the validity of the Country marriage itself. The same applies to the registration status of the children who are born. In addition to the above, another problem that will occur related to the law of Country marriage is the problem of inheritance.